Adjustments of γδ T Cells in the Lung of Schistosoma japonicum-Infected C56BL/6 Mice - Cha, Hefei; Xie, Hongyan; Jin, Chenxi; Feng, Yuanfa; Xie, Shihao; Xie, Anqi; Yang, Quan; Qi, Yanwei; Qiu, Huaina; Wu, Qiongli; Yin, Zhinan; Mu, Jianbing; et al. (Frontiers in Immunology, 2020)
Many kinds of lymphocytes are involved in Schistosoma japonicum (S. japonicum) infection-induced disease. γδ T cells comprise a small number of innate lymphocytes that quickly respond to foreign materials. In this study, the role of γδ T cells in the lung of S. japonicum-infected C56BL/6 mice was investigated. The results demonstrated that S. japonicum infection induces γδ T cell accumulation in the lung, expressing higher levels of CD25, MHCⅡ, CD80 and PDL1, and lower levels of CD127 and CD62L (P<0.05). The intracellular cytokines staining results illustrated higher percentages of IL-4-, IL-10-, IL-21- and IL-6-producing γδ T cells and lower percentages of IFN-γ-expressing γδ T cells in the lung of infected mice (P<0.05). Moreover, the granuloma size in lung tissue was significantly increased in Vδ-/- mice (P<0.05). In the lung of S. japonicum-infected Vδ-/- mice, both type 1 and type 2 immune responses were decreased significantly (P<0.05). In addition, the expression of CD80 and CD69 on B cells was decreased significantly (P<0.05), and the SEA-specific antibody was markedly decreased (P<0.05) in the blood of infected Vδ-/- mice. In conclusion, this study indicates that γδ T cells could adjust the Th2 dominant immune response in the lung of S. japonicum-infected mice.